PERFORMANCE OF KACANG GOATS SUPPLEMENTED WITH BAUHINIA PURPUREA IN COMPLETE FEED - Gerson F. Bira; Alfred Nubatonis; Azor Y. Tefa; Maria M. Kolo (The Iraqi Journal of Agricultural science, 2025)
This research aims to determine the effects and limitations of using B. purpurea in complete feed on the performance of male Kacang goats. The study involved sixteen male Kacang goats aged 10-12 months with a weight range of 12-14 kg. The research method employed a Completely Randomized Design with four treatments and four replications, consisting of T0: G. sepium 30% + Natural grass 38% + Rice bran 7% + Milled corn 24,8% + Mineral mix 0,2% (control); T1: G. sepium 30% + Natural grass 38% + Rice bran 6,5% + Milled corn 22,8% + Mineral mix 0,2% + B. purpurea 2,5%; T2: G. sepium 30% + Natural grass 38% + Rice bran 5% + Milled corn 19,3% + Mineral mix 0,2% + B. purpurea 7,5%; T3: G. sepium 30% + Natural grass 38% + Rice bran 4,5% + Milled corn 14,8% + Mineral mix 0,2% + B. purpurea 12,5%. The results showed that the treatments significantly influenced (P<0,05) blood glucose levels (at 2 and 4 hours after consumption), blood urea levels (at 0 hours before consumption and 6 hours after consumption), crude protein consumption, daily weight gain, weight gain, feed conversion, feed efficiency, and body length. Other variables were not significantly affected. In conclusion, B. purpurea at a concentration of 7.5% yielded the most significant improvements in terms of final body weight, daily weight gain, and feed conversion efficiency.